Educational leadership global contexts and international comparisons - Wiseman, Alexander W., 1968- (Bingley, UK : Emerald, 2009)
This volume of "International Perspectives on Education and Society" investigates the changing face of educational leadership from comparative and international perspectives. Various definitions of leadership have transformed the way that educators around the world think about teaching, administration, and policy in recent years. Yet, there is relatively little known about how educational leadership works in many specific systems, cultures and societies around the world. And, much of the published research and literature on educational leadership focuses on only a handful of countries and cultures even though empirical research suggests that leadership is differently contextualized by society, culture, and organizational environment. The chapters in this volume ask and answer two main questions: What is the difference between theoretical definitions of leadership and what works in different systems, cultures, and societies around the world? And, more importantly, how are both ideas about and evidence of educational leadership either the same or different across different national and cultural contexts?
Leadership for innovative Omani schools in the 21st century: transforming principal identity through culturally contextualized training / Jan M. Westrick and Shirley J. Miske -- The development and role of trust in educational leadership: a comparative study of U.S. and Ugandan school administrators / Pamela R. Hallam ... [et al.] -- Tribalism and its consequences: a cancer infecting the corpus of educational leadership in many West African countries / Samba Moriba and Michael C. Edwards -- Educational leadership in the Niger Delta Region of Nigeria: a study of the perceptions of its impact on the acquired leadership skills of expatriate Nigerian postgraduates / Gerald I. Akata and Jasmine R. Renner -- Antipodean perspectives on enhancing the quality of school leadership: views from Australia and New Zealand / Helen Wildy, Simon Clarke and Carol Cardno -- Analyzing principal influence tactics from a cross-cultural perspective: do preferred influence tactics and targeted goals differ by national culture? / Ibrahim Duyar, Inayet Aydin and Zeki Pehlivan -- Voices from two sides of the Atlantic: women's leadership in Finland and the United States / Eva Anneli Adams -- Developing leaders among women religious in Africa / Mary Salvaterra ... [et al.] -- Successful school principals in Australia and the US: findings from an international study / Rose M. Ylimaki ... [et al.] -- Culture and school leadership in China: exploring school leaders' views of relationship- and rule-based governance / Wing-Wah Law -- Comparisons between transformational leadership and the Confucian idea of transformation / Jingping Sun -- Issues in educational administration in Mexico / José María García Garduño, Charles L. Slater and Gema López Gorosave -- Is 'educational leadership' a national-contextual field of study? Some insights from an analysis of the field's major journals / Izhar Oplatka and Audrey Addi-Raccah.
Includes bibliographical references.
Description based on print version record.
Keywords: Educational leadership; School management and organization; Organization & management of education; Education -- General